Breast Care Behavior with Incidence of Breast Milk Dam in Post Partum Mothers North Bogor - G, Elpinaria; A Yosali, Magdalena; Yuliana; Y G, Salsalina; S, Reny; S, Rizka; M, Tri; T, Sara; R, Eni (Jurnal Keperawatan Respati Yogyakarta, 2025)
The researcher chose the research location at the North Bogor  Sub-Public Health Center because according to the survey that had been conducted and after the researchers conducted brief interviews with people, many people experienced breast milk dams on the first to sixth day after giving birth and there were also many people there who had little knowledge about breast milk dams, did not know the correct breastfeeding position and did not know how to care for their breasts, from January to Juni 2024, there were 180 post-partum mothers and 36(20%) experienced breast milk dams. This research contributed to determine the breast care behavior with incidence of breast milk dam in post-partum mothers north Bogor. This research used analytical research to explores how and why health phenomena occur. The research design used in this study was cross sectional. The sample in this study were all 32 postpartum mothers at the Puskesmas North Bogor. Results were 9 respondents (28.1%), breastfeeding position was good for 22 respondents (68 .8%), knowledge was good for 16 respondents (50%), and breast care for 23 respondents (71.9%) was good. There is a relationship between breastfeeding position and breast milk dams in postpartum mothers at Puskesmas North Bogor Health Center with a p value = 0.001. There is a relationship between knowledge and breast care and breast milk retention in postpartum mothers at the Puskesmas North Bogor with a p value = 0.000. This is in line with the research that the researcher has done, it is suspected that the more you do not do breast care, the more you will experience the risk of breast milk engorgement.